2000
DOI: 10.1038/sj.leu.2401637
|View full text |Cite
|
Sign up to set email alerts
|

Jumping translocation in acute leukemia of myelomonocytic lineage: a case report and review of the literature

Abstract: Jumping translocation (JT) is a very rare cytogenetic event, occurring especially in cancer. We describe a case of secondary acute monocytic leukemia (AML5b) with a JT involving the 3q13-3qter segment and leading to a partial trisomy 3. Each clone with JT was associated with trisomy 8 or tetrasomy 8. The literature of JT in AML cases is reviewed: only 13 cases of AML associated with JT have been previously described, seven of which are AML4/5 FAB subtype. Jumping translocation involvement in leukemogenesis is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 16 publications
4
27
0
Order By: Relevance
“…(q11;q?) [12], add(12)(q14) [4],der (14) Our patient showed no erythroid response to lenalidomide and clonal cytogenetic evolution that was unusual in the 5q-syndrome. The cytogenetic evolution with numerous 5q derivatives resulting from unbalanced translocations between different partners had not, to our knowledge, been previously described, with chromosome 5.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…(q11;q?) [12], add(12)(q14) [4],der (14) Our patient showed no erythroid response to lenalidomide and clonal cytogenetic evolution that was unusual in the 5q-syndrome. The cytogenetic evolution with numerous 5q derivatives resulting from unbalanced translocations between different partners had not, to our knowledge, been previously described, with chromosome 5.…”
mentioning
confidence: 67%
“…It suggests jumping translocations (JT) rarely described in different hematologic malignancies including lymphoma, myeloma, and AML or ALL. 4,5 JT are characterized by relocalization of the same part of a donor chromosome to several recipient chromosomes, usually arising during disease progression or in complex karyotypes, and associated with poor prognosis. 6,7 In our case JT are associated with other abnormalities of chromosome 5.…”
mentioning
confidence: 99%
“…Most JTs have been described as the fusion of a donor segment to the telomere regions of different recipient chromosomes, resulting in nonreciprocal translocations and trisomy or tetrasomy of the donor segment (Bernard et al, 2000). In contrast, Sawyer et al (1998) detected recurring whole-arm JTs (centromere fusions of two chromosome arms) involving the chromosome arm 1q fused to chromosome arms 16q and 19p in 36/158 patients with multiple myeloma and complex karyotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The jumping translocation was initially described by Lejeune et al (1979), whose analysis of chromosomes of a patient with Prader-Willi syndrome revealed that multiple copies of chromosome 15 were fused to the telomere regions of chromosome arms 5q, 8q, and 12q, subsequently forming three unbalanced translocations. A review of the literature reveals that JTs have been described in 135 patients with Crohn's disease, constitutional disorders, and hematological malignancies; in the latter they have been associated with a poor prognosis (Bernard et al, 2000). Chromosome arm 1q was identified as the most common donor in JTs, resulting in trisomies or tetrasomies for this chromosome arm (Sawyer et al, 1998;Busson-Le Coniat et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…JTs are very rare aberrations, usually identified in hematological tumors and are thought to be associated with disease progression and poor prognosis (Keung et al, 1998;Bernard et al, 2000). JTs have been reported also in more than 20 constitutional rearrangements (for review, see Jewett et al, 1998), as well as in chromosome instability syndromes: ataxia telangiectasia (Taylor et al, 1981), xeroderma pigmentosum (Aledo et al, 1989), and Fanconi anemia (Hoffschir et al, 1992).…”
mentioning
confidence: 99%